Congenital Etiology Is an Independent Risk Factor for Complications in Adolescents Undergoing Corrective Scoliosis Surgery: Comparison of In-hospital Comorbidities Using Nationwide KID's Inpatient Database. Issue 8 (September 2019) - Poorman, Gregory W.; Jalai, Cyrus M.; Diebo, Bassel; Vira, Shaleen; Buza, John; Baker, Joe; Tishelman, Jared; Horn, Samantha; Bono, Olivia; Shenoy, Kartik; Hasan, Saqib; Paul, Justin; et al.
Abstract : Background: Congenital scoliosis (CS) is associated with more rigid, complex deformities relative to adolescent idiopathic scoliosis (AIS) which theoretically increases surgical complications. Despite extensive literature studying AIS patients, few studies have been performed on CS patients. The purpose of this study was to evaluate complications associated with spinal fusions for CS and AIS. Methods: A retrospective review of the Kid's Inpatient Database (KID) years 2000 to 2009 was performed. Inclusion: patients under 20 years with ICD-9 diagnosis codes for idiopathic scoliosis (IS—without concomitant congenital anomalies) and CS, undergoing spinal fusion from the KID years 2000 to 2009. Two analyses were performed according to age below 10 years and 10 years and above. Univariate analysis described differences in demographics, comorbidities, intraoperative complications, and clinical values between groups. Binary logistic regression controlling for age, sex, race, and invasiveness predicted complications risk in CS (odds ratios; 95% confidence interval). Results: In total, 25, 131 patients included (IS, n=22443; CS, n=2688). For patients under age 10, CS patients underwent 1 level shorter fusions ( P <0.001), had fewer comorbidities ( P <0.001), and sustained similar complication incidence. In the 10 and over age analysis, CS patients similarly had shorter fusions, but greater comorbidities, and significantly more complications (odds ratio, 1.6; confidence interval, 1.4-1.8). Conclusions: CS patients have higher in-hospital complication rates. With more comorbidities, these patients have increased risk of sustaining procedure-related complications such as shock, infection, and Adult Respiratory Distress Syndrome. These data help to counsel patients and their families before spinal fusion. Level of Evidence: Level III—retrospective review of a prospectively collected database. Abstract : Supplemental Digital Content is available in the text.